Implementation of Pharmacogenetics in Primary Care: A Multi-Stakeholder Perspective - Rigter, Tessel; Jansen, Marleen E.; Groot, Jordy M. de; Janssen, Susan W.J.; Rodenburg, Wendy; Cornel, Martina C. (Frontiers in Genetics, 2020)
Aberrant pharmacogenetic variants occur in a high proportion of people and might be relevant for the prescription of over 26 drugs in primary care. Early identification of patients who metabolize these drugs more rapidly or slowly than average could predict therapeutic effectivity and safety. Yet implementation of pharmacogenetics is progressing slowly. A high public health impact can potentially be achieved by increasing the proportion of people tested, when and where eligible according to clinical validity and utility. In this study we defined actions, roles, and responsibilities for implementation of pharmacogenetics in primary care in consultation with stakeholder groups, by using a three-step mixed-methods approach. First, to define barriers and facilitators, public pharmacists (n=24), primary care physicians (n=8), and patients (n=21) participated in focus groups and face-to-face interviews. Second, a multidisciplinary expert meeting (n= 16) was organized to define desired actions, roles and responsibilities. Third, an online Delphi study (n=18) was conducted to prioritize the designated actions. For the integration of pharmacogenetics in primary care guidelines and practice, lack of evidence for clinical utility was mentioned as a main barrier. Furthermore, reimbursement, and facilitation of data registration and sharing were considered as key elements for future routine application of pharmacogenetic testing. Moreover, the division of roles and responsibilities, especially between general practitioners and pharmacists, is currently perceived as unclear. Sixteen actions in these four areas (clinical utility; reimbursement; data registration and sharing; roles and responsibilities) were formulated and assigned to specific actors during the expert meeting. After ranking these sixteen actions in the Delphi study, nine actions remained pertinent, covering the four areas with at least one action. However, participants showed low agreement on the prioritization of the different actions, illustrating their different perspectives and the need to attune between them. Stakeholders together were able to formulate required actions to achieve true integration of pharmacogenetics in primary care, but no consensus could be achieved on the prioritization of the actions. Coordination of the current independent initiatives by the different stakeholders could facilitate effective and efficient implementation of useful pharmacogenetics in primary care.